2007
DOI: 10.1109/iembs.2007.4353072
|View full text |Cite
|
Sign up to set email alerts
|

Area Assessment of Psoriasis Lesion for PASI Scoring

Abstract: Psoriasis is a skin disorder which is caused by genetic fault. There is no cure for psoriasis, however, there are many treatment modalities to help control the disease. To evaluate treatment efficacy, PASI (Psoriasis Area and Severity Index) which is the current gold standard method is used to measure psoriasis severity by evaluating the area, erythema, scaliness and thickness of the plaques. However, the calculation of PASI can be tedious and subjective. In this work, we develop a computer vision method that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Fvirthermore, only 4 out of the 23 studies reviewed used clinical measures such as PASI and PDI. It has been shown that PASI is one of the most important clinical tools available for objectively assessing the magnitude of beneflt resulting from a psoriasis treatment (62). Future studies should therefore employ clinical measures, since dermatologists emphasize the importance of clinically observable criteria (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Fvirthermore, only 4 out of the 23 studies reviewed used clinical measures such as PASI and PDI. It has been shown that PASI is one of the most important clinical tools available for objectively assessing the magnitude of beneflt resulting from a psoriasis treatment (62). Future studies should therefore employ clinical measures, since dermatologists emphasize the importance of clinically observable criteria (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The dependent variables were assessed t 1 , t 2 (twelve weeks post-t 1 ) and t 3 (twelve weeks post-t 2 ). Twelve weeks are known to be sufficient to judge the short-term effectiveness of a psoriasis treatment, but we specifically wanted to look at longer-term outcomes at 24 weeks which may better represent sustainable treatment adherence [17]. Our analyses therefore focused on changes observed between t 1 and t 3 , although additional analyses (not described here) were also performed for changes observed between t 1 and t 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The PASI is a psychometrically valid and reliable instrument routinely applied in dermatology to assess psoriasis severity and gauge treatment effects [17]. PASI combines assessment of the severity of psoriasis lesions and the area affected into a score ranging from 0 (no disease) to 72 (maximal disease), with scores ≥ 10 reflecting moderate to severe disease [17]. …”
Section: Methodsmentioning
confidence: 99%
“…The dermatologist examined the child, confirmed the psoriasis diagnosis, and classified the psoriasis (guttate, plaque, inverse, erythrodermic, pustular, psoriasis with arthritis). The dermatology research nurse assessed the psoriasis with the Psoriasis Area and Severity Index (PASI) (13).This is the current gold standard method for scoring the severity of psoriasis, by estimating the area, erythema, scaling, and thickness (14). Prior to the study, the dermatologists and the dermatology research nurse had trained in and agreed on how to perform the scoring.…”
Section: History and Examinationmentioning
confidence: 99%